A methodology and computational system for the simulation of fluid-structure interaction problem - Antunes,A. R. E. (2005)
In this paper a flexible finite element computational tool developed to investigate fluid-structure interaction applications in two dimensions is described. We consider problems which can be modelled as a viscous incompressible fluid flow and a rigid body-spring system interacting nonlinearly with each other. The coupling is dealt with the use of an interface approach, in which each physics involved is solved with different schemes and the required information is transferred through the interface of both systems. This approach is, at least in principle, very flexible and computationally efficient as the best available scheme can be adopted to solve each physics. Here, a stabilized FEM considering the "ALE" (Arbitrary Lagrangian-Eulerian) formulation with Crank-Nicholson time-integration is employed for the fluid-dynamics analysis, and the Newmark Method is used for the structural dynamics. Several important tools were incorporated into our system including different possibilities for the mesh movement algorithm, the computational domain decomposition into regions with and without mesh deformation, and the remeshing strategy (either global or local) to keep the necessary mesh quality. As application we present a study of the forced lock-in phenomena and a preliminary investigation on the suppression (or at least the reduction) of the vortex induced vibrations (VIV) on a solid circular cylinder using an idealization of a periodic acoustic excitation.